1997
DOI: 10.1108/09564239710166254
|View full text |Cite
|
Sign up to set email alerts
|

A dual perspective of customer orientation: a modification, extension and application of the SOCO scale

Abstract: The importance of customer orientation has been widely discussed although few studies have specifically measured this construct. Describes a study that compares the service providers’ self‐perception of customer orientation with customer perceptions of this dimension in a health care setting where both nurses and patients are surveyed. Customer orientation is measured using a modified SOCO scale adapted to a hospital context. Finds significant differences between the nurses’ and patients’ mean scores for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 50 publications
(72 reference statements)
2
37
0
4
Order By: Relevance
“…Extensive research supports the validity of the original 24-item scale and variations in its format, including using fewer items (Daniel & Darby, 1997;Williams & Attaway, 1996). We selected 10 items that best reflected employees' customer-oriented service behaviors (rather than beliefs), were stem-positively stated (to avoid potential respondent confusion), and could be most readily adapted to the ISO service context.…”
Section: Customer-oriented Service Behaviormentioning
confidence: 95%
“…Extensive research supports the validity of the original 24-item scale and variations in its format, including using fewer items (Daniel & Darby, 1997;Williams & Attaway, 1996). We selected 10 items that best reflected employees' customer-oriented service behaviors (rather than beliefs), were stem-positively stated (to avoid potential respondent confusion), and could be most readily adapted to the ISO service context.…”
Section: Customer-oriented Service Behaviormentioning
confidence: 95%
“…Past research demonstrated both the scale's reliability and validity (Saxe and Weitz 1982, Hoffman and Kelley 1994, Daniel and Darby 1997. It measures customer orientation from a behavioural point of view (Saxe andWeitz 1982, Daniel andDarby 1997). It involves aspects like 'helping customers assess their needs', or 'avoiding deceptive or manipulative influence tactics' (Saxe and Weitz 1982, p. 344).…”
Section: Distinguish Betweenmentioning
confidence: 96%
“…As self-report measure for participants' customer orientation, the 24-item 'Selling Orientation -Customer Orientation Scale' (¼SOCO Scale; Saxe and Weitz 1982) was used. Past research demonstrated both the scale's reliability and validity (Saxe and Weitz 1982, Hoffman and Kelley 1994, Daniel and Darby 1997. It measures customer orientation from a behavioural point of view (Saxe andWeitz 1982, Daniel andDarby 1997).…”
Section: Distinguish Betweenmentioning
confidence: 97%
“…In the healthcare context, it is explained that the term customer-oriented behavior refers to the service behavior and ability of the care providers to adjust their service in order to reflect patients' reality [4]. On the same note, researchers [5] stated that nurse-patient interface embraces elements of the nurse-patient interaction in the process of co-producing a service.…”
Section: A Definitions and Conceptsmentioning
confidence: 99%